PENERAPAN MORNING BRIEFING PADA OPERASIONAL PERUSAHAAN PT AGRODANA FUTURES SURABAYA IMPLEMENTATION OF MORNING BRIEFING IN PT AGRODANA FUTURES SURABAYA COMPANY OPERATIONS - Anindito, Aryo; Zawawi, Zawawi (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Morning Briefing is a short meeting held routinely in the morning before starting the workday, where all employees of PT Agrodana Futures Surabaya gather to discuss the day's work plans and share important information from the previous day, such as the results of fundamental and technical analysis, as well as news on global trade. PT Agrodana Futures Surabaya conducts morning briefings with the aim of ensuring that all employees are well-prepared before meeting prospective clients and to evaluate the work completed on previous days. Additionally, boosting employee motivation at the end of each session is another key benefit of the morning briefing. The company's operations are significantly impacted by the outcomes of the morning briefing held each day, as a company can operate effectively and efficiently when its employees are highly motivated.